2016
DOI: 10.1002/wrna.1381
|View full text |Cite
|
Sign up to set email alerts
|

Modulating splicing with small molecular inhibitors of the spliceosome

Abstract: Small molecule inhibitors that target components of the spliceosome have great potential as tools to probe splicing mechanism and dissect splicing regulatory networks in cells. These compounds also hold promise as drug leads for diseases in which splicing regulation plays a critical role, including many cancers. Because the spliceosome is a complicated and dynamic macromolecular machine comprised of many RNA and protein components, a variety of compounds that interfere with different aspects of spliceosome ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
135
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(139 citation statements)
references
References 131 publications
(271 reference statements)
2
135
1
1
Order By: Relevance
“…Although a series of studies have produced materials with increased stability,[22, 53] often these compounds are significantly less effective at modulating RNA splicing. [24––28] As illustrated in the current SAR maps (Figure 5),[19] only a small number of analogues, such as 23 (Figure 6), have been identified that offer enhanced activity over their natural product counterparts.…”
Section: Resultsmentioning
confidence: 99%
“…Although a series of studies have produced materials with increased stability,[22, 53] often these compounds are significantly less effective at modulating RNA splicing. [24––28] As illustrated in the current SAR maps (Figure 5),[19] only a small number of analogues, such as 23 (Figure 6), have been identified that offer enhanced activity over their natural product counterparts.…”
Section: Resultsmentioning
confidence: 99%
“…Altogether, current findings represent only a starting point for fully understanding the mechanistic effects of recurrent splicing factor mutations. Future efforts to elucidate these possibilities would guide longer-term efforts to exploit the therapeutic potential of spliceosome inhibitors [90], as recently highlighted by the spliceosome-sensitivity of MYC-driven cancers [9193]. …”
Section: Discussionmentioning
confidence: 99%
“…To date, spliceostatin A, meayamycin, and pladienolide B are part of a well-characterized group of small-molecule splicing inhibitors (for a recent review, see Effenberger et al, 2016). These compounds target a specific spliceosome component, the U2 snRNP SF3b complex, and were originally discovered as substances that inhibited the growth of human tumors (Nakajima et al, 1996).…”
Section: Discussionmentioning
confidence: 99%